alex-huth/Simulating_Larsen_C_Rift_Paths: Initial release ... - Huth, Alex (Zenodo, 2023)
Initial release: The model source code, input data, and experiment setups needed to run the forward simulations in Huth et al (2023). "Simulating the processes controlling ice-shelf rift paths using damage mechanics". Journal of Glaciology. ...